Investigation on electrochemical properties of CNTs/Si composites as anode in lithium ion batteries / Kevin Alvin Eswar - Eswar, Kevin Alvin (2008)
In this study, lithium metal is used as cathode and 1 M LiPF6 + DMC: EC (1:1) as a liquid electrolyte. In order to investigate the anode, six samples with different amount of CNTs composite's are prepared by ultrasonic bath method. The six samples are Sample A (pure CNTs) as received, Sample B (99.5% wt. CNTs, 0.5% wt. Si), Sample C (99% wt. CNTs, 1% wt. Si), Sample D (98% wt. CNTs, 2% wt. Si), Sample E (97% wt. CNTs, 3% wt. Si) and Sample F (95% wt. CNTs, 5% wt. Si). Electrochemical properties; cyclic voltammetry and charge-discharge are carried out by using battery cycler (Won a Tech) in range 0V-3V, current 0.2 mA and limited to 25 cycles. The charge-discharge study shows the capacity loss is minimum starting from the second cycle of all samples. It is also shows the columbic efficiency is very good where 96 % of capacities are retained after 25 cycles. The cyclic voltammetry is studied to investigate the redox reaction of sample. It shows the good redox reaction for entire samples.